Fellini Satyricon [videorecording (DVD)] - Fellini, Federico; Potter, Martin; Keller, Hiram, 1944-1997; Petronius Arbiter (World films., 2001)
Fellini recreates the bawdy and lecherous days of Nero's reign in ancient Rome and its lack of concern with human dignity and obsession with perverse sex. The film is also an allegorical satire of the self-indulgence of modern society.